The impact of psychiatric disorders on caregivers: An integrative predictive model of burden, stigma, and well‐being. Issue 4 (28th March 2022) - Radu, Mădălina; Ciucă, Andrada; Crișan, Cătălina‐Angela; Pintea, Sebastian; Predescu, Elena; Șipos, Roxana; Moldovan, Ramona; Băban, Adriana
Abstract: Purpose: The study investigates the predictors of caregivers' experienced burden, stigma, and well‐being, when looking after family members diagnosed with a psychiatric disorder. Design and Methods: This cross‐sectional study included 168 caregivers; perceived burden, stigma, well‐being, knowledge, illness perception, and medical variables were assessed. Findings: A number of correlates of burden, stigma, and well‐being have been identified and are being discussed. The integrative predictive model showed that the caregiver's emotional representation of illness best predicts burden ( β = 0.38, p < 0.001), stigma ( β = 0.53, p < 0.001) and well‐being ( β = −0.36, p < 0.001). Practice Implications: Our results can enable health professionals to tailor psychosocial interventions addressed to family members of individuals living with a psychiatric condition.